The Role of Telomerase in Celullar Senescence and Its Implications For Anti-Aging Therapy - Ratna Shintia Defi; Henrita Ernestia; Ferdinandus Krisna Pukan (Pattimura University, 2025)
Aging is a complex biological process influenced by genetic, environmental, and lifestyle factors. One of the primary mechanisms contributing to aging is telomere shortening, which plays a crucial role in genome stability and cellular regeneration. As individuals age, progressive telomere shortening can trigger cellular apoptosis and tissue dysfunction, impacting health and skin aesthetics. Consequently, telomere-based anti-aging therapies have become a significant focus of strategies aimed at slowing the aging process and improving quality of life. Several studies have explored various therapeutic approaches, including telomerase activation, bioactive compounds, and genetic engineering technologies to maintain telomere length and enhance cellular function. This literature review aims to analyze recent developments in telomere-based anti-aging therapies, evaluate their effectiveness, and discuss their potential applications in health and aesthetic medicine. A deeper understanding of telomere mechanisms and their therapies is expected to facilitate the development of more effective and sustainable anti-aging strategies.